(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2020)
This article is the result of dialogue and interaction with Carolina Garcia, actress and producer of the theatre play Habite-me (2019). The show, defined as theater of masks, dance and puppets, has a prologue and three parts, and deals with existential themes, such as life and death, the relationship with the passage of time and care for others. The proposal, by enlivening these themes and intertwining them with a woman’s body, also engages in a dialogue with the other elements of the scene, acquiring different contours and expanding them. Habite-me is the result of an exchange between artists from Brazil, Canada (Cie.Territoire 80) and Belgium.